ABC News - Nightline: All That Remains
Ted Koppel and Dave Marash discuss and present the work of detective medics and human rights physicians who try to collect evidence and identify individuals from the mass graves in Bosnia. The program features interviews with doctors of the "Physicians for Human Rights", officials and volunteers present at the massacre scenes, including John Shattuck, at the time Assistant Secretary of State for Human Rights.